2018
DOI: 10.1177/0300060518800652
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of idiopathic pulmonary hemosiderosis in pediatric patients

Abstract: Objective This study aimed to analyze the clinical characteristics and prognosis of pediatric idiopathic pulmonary hemosiderosis (IPH). Methods Pediatric IPH cases that were diagnosed at West China Second University Hospital, Sichuan University between 1996 and 2017 were reviewed. Follow-up data from 34 patients were collected. Results A total of 107 patients were included (42 boys and 65 girls). The median age was 6 years at diagnosis. The main manifestations of the patients were as follows: anemia (n = 100, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
2
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 41 publications
1
71
2
13
Order By: Relevance
“…Our knowledge in terms of mechanisms underlying recurrent episodes in IPH is very limited 17 . The worsening of the clinical course may be due to both the primary underlying mechanism and triggering factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our knowledge in terms of mechanisms underlying recurrent episodes in IPH is very limited 17 . The worsening of the clinical course may be due to both the primary underlying mechanism and triggering factors.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicated that recurrent episodes were frequent in children with IPH. Only one recent study has attempted to identify predictors for recurrence episodes in patients with IPH 17 . They compared results of 10 patients with recurrence episodes, and 22 patients who healed or improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ere is a long delay (4 months-10 years) between onset of the symptoms and diagnosis [2,5,6,10]. Especially, in young children, hemoptysis is not common as the first symptom of IPH, occurred in about 50% of patients [10,16], who swallow hemorrhage sputum. In many reports, shortness of breath, iron deficiency anemia, and alveolar infiltration on chest X-ray are typically seen [17].…”
Section: Discussionmentioning
confidence: 99%
“…1C and D). The patient has been closely monitored due to the high relapse incidence of IPH (18) and remained in remission at the time of the last follow-up in November 2019.…”
Section: Case Reportmentioning
confidence: 99%